Re-examining UNTAG’s humanitarian role in Namibia’s transition: Life stories of former SWAPO exiles during and after repatriation (Journal of Namibian Studies : History Politics Culture, 2022)
The personal stories of former SWAPO exiles reveal how UNTAG’s limited role in Namibia’s transition had lasting effects that shaped the reintegration processes for former SWAPO exiles in the post-colony. The purpose of this paper is to map the life histories of former SWAPO exiles in order to understand their lived experiences of repatriation and its aftermath. These life histories were obtained through semi-structured interviews that mapped their individual trajectories from 1989 through 2018. The life histories mapped in this paper invite the reader to consider the prospect that the benefits of UNTAG’s humanitarian support to returning SWAPO exiles have been exaggerated.